Eosinophilic Gastrointestinal Disorder in Coeliac Disease: A Case Report and Review - Dennis N. F. Lim; Annelise Wilkins; Laura Elizabeth Horton; Ishfaq Ahmad; Catherine lo Polito; Chris Phillips (Case Reports in Gastrointestinal Medicine)
Eosinophilic gastrointestinal disorder is a rare disorder characterised by eosinophilic infiltration of the gastrointestinal tract. There are various gastrointestinal manifestations with eosinophilic ascites being the most unusual and rare presentation. Diagnosis requires high index of suspicion and exclusion of various disorders associated with peripheral eosinophilia. There are no previous case reports to suggest an association between eosinophilic gastrointestinal disorder and coeliac disease in adults. We report a case of eosinophilic ascites and gastroenteritis in a 30-year-old woman with a known history of coeliac disease who responded dramatically to a course of steroids.